Male Partner’s Involvement in HIV Counselling and Testing and Associated Factors among Partners of Pregnant Women in Gondar Town, Northwest Ethiopia - Alemu Zenebe; Abebaw Gebeyehu; Lemma Derseh; Kedir Y. Ahmed (Journal of Pregnancy)
Background. Despite the existence of several programmes promoting male involvement in HIV counselling and testing during their wife’s pregnancy as a part of PMTCT, few men have heeded the call. The aim of this study was to assess male partner’s involvement in HCT and its associated factors. Methods. This study was based on institution based cross-sectional study design that used systematic random sampling technique. A total of 416 partners were interviewed in the data collection. Multivariable logistic regression model was fitted to identify the independent predictors. Result. In this study, the prevalence of male involvement in HCT was found to be 40.1% (95% CI: 35.3%–44.7%). The independent predictors of male involvement were partners who were younger, were cohabitant, were with multigravida wives, were knowledgeable on route of mother-to-child transmission, and discussed HCT. Conclusion. The prevalence of male involvement in HCT was found to be suboptimal compared to similar studies in Ethiopia. There is a need of interventions on partners who are older, separated, and with lower gravidity wife. Awareness creation campaign should also be created on the route of mother-to-child transmission of HIV and on the importance of discussion with wife.